Synthesis and Characterization of Schiff Base Derivatives of Organoheterobimetallic dibutyl [Sn(IV); B(III)]-\(μ\)-oxoisopropoxide - Jashmer Singh (Advancements in Science and Technology: Paving the Way to a Sustainable Future, 2025)
A number of reactions of organoheterobimetallic dibutyl[Sn(IV); B(III)] \(μ\)-oxoisopropoxide with bidentate Schiff bases (HSB) i.e Salicylidene aniline (HSB1), Salicylidene-o-toluidene (HSB2) and Salicylidene-p-chloroaniline (HSB3) are performed in different molar ratios (1:1-1:2) in refluxing benzene results in the formation of products of the type [Bu2SnO2B2(O-i-Pr)4-n(SB)n] (where n = 1-2 ). The isopropanol liberated during the course of reaction is collected azeotropically (isopropanol-benzene) and estimated oxidimetrically to check the progress of the reaction. The derivatives have been characterized by elemental, liberated isopropanol and spectral analysis (IR, 1H, 13C,119Sn and 11B NMR). All the Schiff base derivatives are found to be brownish yellow highly viscous liquid to gel type, soluble in organic solvents and susceptible to hydrolysis.